Response of characteristic hormones in tea roots and leaves under magnesium regulation and their balancing regulation on growth and quality - Jia, Xiaoli; Wang, Yulin; Wang, Tingting; Zhu, Bitong; Weng, Qiqi; Liao, Yankun; Gu, Junbin; Luo, Yangxin; Zhang, Qi; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2026)
Magnesium (Mg) plays a critical role in tea plant growth, profoundly affecting their development and leaf quality. In our study, we used hormone metabolomics technology to identify characteristic hormones that underwent significant changes in roots and leaves of tea plant when subjected to variations in Mg contributions. The results showed that characteristic hormones in leaves regulated by Mg were L-phenylalanine and indole, which positively regulated leaf resistance (0.942**), nutrient accumulation capacity (0.935**), photosynthesis capacity (0.917**) and plant height (0.921**). The characteristic hormones of the root were L-tryptophan, L-phenylalanine, indole and 2-methoxycarbonylphenyl beta-D-glucopyranoside, which positively regulated root resistance (0.940**), root vigor (0.948**), nutrient accumulation capacity (0.963**) and root growth index (0.917**). In contrast, exogenous treatments of characteristic hormones obtained from roots and leaves all effectively promoted tea quality and tea plant growth. It is obvious that with the increase of Mg concentration, tea plants synthesized a large number of characteristic hormones, which promoted their rapid growth, but reduced leaf quality, while exogenous treatment of the characteristic hormones to tea plants could promote their growth, and also improve leaf quality. The research provides valuable insights for achieving high-yield and high-quality cultivation for tea plants.